Mafalda outra vez: as tirinhas de quino como recurso didático- pedagógico para promover a atitude historiadora no Centro de Excelência Cleonice Soares Fonseca, Boquim-SE - Santos, Gilvânio Fontes (2025)
This dissertation examines how Mafalda's comic strips contribute to the teaching of History at the Centro de Excelência Cleonice Soares Fonseca, in Boquim, Sergipe. The research is justified by the need to understand how this resource can aid in promoting a critical and reflective approach to teaching the subject. The overall objective is to analyse Mafalda’s comic strips in the context of the relationship between history and education in the current educational framework. The methodology employed is qualitative, combining a literature review and document analysis. The study is structured into three chapters. In the first chapter, "As Tirinhas de Mafalda e Quino: Imagem e Educação Visual", I discuss the importance of visual education and the historian’s attitude in the teaching of History, engaging with key authors in the field. In the second chapter, "Educação Visual: As Tirinhas de Mafalda Como Recurso Didático- pedagógico no Ensino de História", I explore Quino’s biography, the definition of Comics (HQs), and the potential of Mafalda’s comic strips as a pedagogical tool for constructing historical knowledge. Additionally, I address the context in which these comics were created. In the third chapter, "Cartilha de Atividades e Atitude Historiadora Através da Personagem Mafalda", I investigate conventional educational practices in the teaching of History and propose an Activity Workbook based on Mafalda’s comic strips to foster a more critical and reflective approach. In the Final Considerations, I summarise the results obtained and their implications for the teaching of History at the analysed institution. This study aims to contribute to more effective and meaningful educational practices, encouraging the historian’s attitude through Mafalda’s comic strips as a pedagogical tool.